Hyperthermic Syndrome in Children: Mechanisms of Development, Features of Its Course, Treatment Methods - O.Ye. Chernysheva; Ye.I. Yulish; B.I. Krivuschev; Yu.A. Soroka (Zaslavsky O.Yu., 2012)
The article deals with causes, mechanisms of development, features of course and approaches to therapy of hyperthermic syndrome in children.